RELIABILITY APPROACH OF DATA GATHERING PROTOCOL FOR MOBILE USERS IN WIRELESS SENSOR NETWORK (International Journal of Engineering and Computer Science, 2017)
In today’s world people interact with the network and collects data from network with the help of handheld devices. Here we propose a novel approach for the mobile users to collect data network wide. Most of the traditional Wireless Sensor Network (WSN) architectures consist of static nodes which are densely deployed over a sensing area. The route structure of data collection is updated every time when the movement of the mobile user changes. By considering this approach we perform limited modification to update the route structure while the route performance is bounded and controlled compared to the optimal performance in the Wireless Sensor Network. In this we need to update the route structure of data collection whenever there is mobile movement. The proposed protocol to update route structure is easy to implement. The protocol uses three approaches as: Initialization of data collection tree, Updation of data collection tree, Routing of data. Our analysis generated the above mentioned protocol is use to shows that the proposed approach is scalable in maintenance overheads, performs efficiently in the routing and provides continuous data delivery during the movement of the user. Finally we examine the efficiency of our protocol by varying the settings of networks which provides the efficient way of data collection using wireless sensor network.